ANALISIS KETERAMPILAN BERBICARA PESERTA DIDIK MELALUI PENGGUNAAN CERITA ANAK BERBASIS FLIPBOOK - Amalia, Tiana; Amelia, Decenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to describe the early speaking skills of third-grade students at SDN Harapan Baru 01, Bekasi City, in the 2025/2026 academic year. This study used a descriptive qualitative approach. Data were obtained from teachers and third-grade students. Data were collected using observation techniques, informal interviews with teachers, and oral tests. The results revealed that most students still have low early speaking skills, both in terms of fluency, word choice, sentence structure, intonation, and facial expressions. This condition indicates the need for more supportive learning approaches, such as project-based learning, role-playing, simple interviews, storytelling methods, and the use of media such as flipbook-based children's stories, podcasts, and audiovisuals, which can also be applied as innovative and enjoyable learning approaches. This research is expected to provide a basis for designing more effective methods or approaches to teaching speaking at the elementary school level.